2018
DOI: 10.1016/j.virusres.2018.07.020
|View full text |Cite
|
Sign up to set email alerts
|

The canonical Wnt/β-catenin signaling pathway stimulates herpes simplex virus 1 productive infection

Abstract: The ability of herpes simplex virus 1 (HSV-1) to replicate efficiently in differentiated cells is regulated by cellular factors that stimulate viral gene expression, cell survival, and viral morphogenesis. Activation of the canonical Wnt signaling pathway generally increases β-catenin protein levels, cell survival, and growth in dividing cells suggesting this important signaling pathway regulates productive infection. In this study, we demonstrated that a β-catenin specific small molecule inhibitor (iCRT14) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…In accordance with its impact on late viral gene expression, β-catenin inhibition significantly reduced viral progeny formation (Figure 7F). This is in agreement with a recent report by Zhu and Jones (2018) showing iCRT14-reduced plaque formation in two other cell types (HLF and Vero). Similar results were obtained when β-catenin was silenced using siRNA (Figure 7G,H).…”
Section: Resultssupporting
confidence: 94%
“…In accordance with its impact on late viral gene expression, β-catenin inhibition significantly reduced viral progeny formation (Figure 7F). This is in agreement with a recent report by Zhu and Jones (2018) showing iCRT14-reduced plaque formation in two other cell types (HLF and Vero). Similar results were obtained when β-catenin was silenced using siRNA (Figure 7G,H).…”
Section: Resultssupporting
confidence: 94%
“…Numerous protein interactions and regulators of β-catenin have been characterized, with one known transcriptional co-activator being CBP for DNA binding. The association between this prosurvival factor and infection remains understudied as only a small number of studies exist linking HSV-1 or other viral infection to β-catenin activation (42)(43)(44). In this study, we show that multiple commercially available compounds targeting CREB and β-catenin systems demonstrate antiviral efficacy against HSV-1.…”
Section: Discussionmentioning
confidence: 74%
“…These proteins are central components of the Wnt/beta-catenin signaling pathway. Previous studies revealed that activation of the Wnt/beta-catenin signaling pathway could stimulate viral replication 41,42 , and inhibition of this pathway could reduce the viral yield during productive viral infection 43,44 . Moreover, we showed that NSP10 interacts with several factors involved in the ERK1/ERK2 signaling pathway ( Figure 2 ), implying that SARS-CoV-2 may hijack the MAPK-ERK pathway to control the cell fate for the viral lifecycle, as reported for other viruses 45 .…”
Section: Resultsmentioning
confidence: 99%
“…These proteins are central components of the Wnt/beta-catenin signaling pathway. Previous studies revealed that activation of the Wnt/beta-catenin signaling pathway could stimulate viral replication 41,42 , and inhibition of this pathway could reduce the viral yield during productive viral infection 43,44 .…”
Section: Sars-cov-2 Controls the Host Cell Metabolism And Signaling Pmentioning
confidence: 99%